قيس بن أبي حازم ومروياته في السنن الأربعة : دراسة نقدية - محمد، أحمد حسن (bKulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This thesis centers on one of the best narrators among those who came after the Companions of Prophet Muhammad (saw). He is Qeis Ibn Abi Hazim Albajali Al-Ahmisi, who migrated to Madina to give his pledge to Prophet Muhammad (saw) but, unfortunately, Muhammad (saw) had passed away a few days before he reached Madina. Qeis who gained the opportunity to narrate from those Ten who attained the glad tidings to paradise, was also referred to by Imam Al-Bukhari and Imam Muslim. In addition, he was well-known for his unique chain that some were not, even though some observations had been raised against him, questioning his act of innovation and memory disorder upon his competence. Some of these issues remain controversial but no fact has been established about them. However, this thesis elaborates more on this special personality for his distinction among Hadith narrators, and also to purge all that has been negatively said against him.The thesis analyses, readdresses and gives much weight on that, and again sheds light on his narrated Hadiths in The Four Sunan through a critical approach with explanation on their rank, and more to what they do in intellectual studies.